THE ROLE OF AI IN PERSONALIZING DIGITAL MARKETING CAMPAIGNS: A TECHNICAL ANALYSIS - Rohith Vangalla, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive technical article examines the transformative role of Artificial Intelligence in personalizing digital marketing campaigns. The article explores various aspects of AI implementation in marketing, including core technologies like machine learning algorithms, natural language processing, and deep learning networks. It investigates data processing architectures, implementation mechanisms, real-time optimization strategies, and measurable impacts across different marketing domains. The article also addresses critical aspects of technical requirements, privacy considerations, and compliance frameworks necessary for successful AI marketing implementation. Through extensive analysis of current research and industry practices, this article demonstrates how AI-driven personalization is revolutionizing marketing effectiveness while highlighting the importance of balancing technological innovation with privacy protection and human expertise.